HUBUNGAN POLA AKTIVITAS FISIK DENGAN STATUS NUTRISI PADA SISWA KELAS X TAHUN AJARAN 2014-2015 DI SEKOLAH MENENGAH KEJURUAN NEGERI 5 DENPASAR - Andrewartha, Gede; Saraswati, Made Ratna (E-Jurnal Medika Udayana; Vol 6 No 3 (2017): E-jurnal medika udayana, 2017)
Obesity or overweight is a condition accumulation of excess fat in the body that can interfere health. Overweight by category Overweight, Obese I, II and Obese caused by many factors such as genetics, diet, physical activity, and environmental factors. Physical activity is one of the factors trigger more nutrition. The pattern of sedentary life (mild physical activity) caused by increasingly advanced technology led to a decrease in physical activity in adolescents. Assessment of physical activity patterns is important to note because some studies have demonstrated an association between physical activity and obesity. The purpose of this thesis is to determine whether there was a relationship between physical activities with body mass index in adolescents. This study used a cross-sectional design with a sample size of n = 100 samples. The results showed respondents with low levels of physical activity were 68% and respondents with moderate physical activity was 32%. Respondents with a body mass index was classified as overweight and 22% of respondents with non-obese body mass index is 68%. The result of the chi-square statistical analysis on the relationship of physical activity with body mass index shows the value of p = 0.116. From the results of this study concluded that the majority of respondents have a light physical activity. And the prevalence of overweight among respondents was 22%. These results suggest there is no relationship between physical activity and nutritional status of the respondents
Keywords: nutritional status, physical activity, obesity.